Konstruksi Banten Gebogan pada Era Golobalisasi di Desa Abiantuwung, Kecamatan Kediri, Kabupaten Tabanan - Pande Putu Toya Wisuda; I Nyoman Subrata (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2021)
Banten is the means used by Balinese Hindus to worship God. One of them is the banten gebogan. Banten gebogan now a days uses not only fruits, snacks, flowers and other food products, but has begun to use factory made canned drinks. Three formulations of the problem can be stated, namely (1) What is the form of banten gebogan in the era of globalization in Abiantuwung Village, Kediri District, Tabanan Regency? (2) Why in the era of globalization, the people of Abiantuwung Village, Kediri District, Tabanan Regency use a variety of canned drinks in making offerings of gebogan? and (3) What are the implications of offering banten gebogan in the era of globalization in Abiantuwung Village, Kediri District, Tabanan Regency? This research use a qualitative approach. The data collection technique was done by observing, interviewing, and studying documents. The validity of the data was obtained by using the transcription technique. The informants are determined in a proposive manner, and the researcher himself is the main instrument assisted by an interview guide, digital camera, laptop, and writing instruments. After verification, the data were analyzed using two theories, namely the theory of globalization and the theory of sociocultural systems. The form of banten gebogan can be divided into two parts according to the times, namely Banten Gebogan Traditional and Banten Gebogan Modern. As for the reasons that make people make modern offerings, namely: Yajña Offerings of Gratitude to God, Art and Aesthetic, and Practical, Effective and Efficient. The implications of this modern offering is the spiritual degradation and cultural transformation.